A New Electrospray Aerosol Generator with High Particle Transmission Efficiency - Fu, Huijing (Aerosol science and technology : the journal of the American Association for Aerosol Research, 2011)
A new single-capillary electrospray (ES) aerosol generator has been developed for monodisperse particle production with maximal transmission efficiency. The new generator consists of both a spray chamber in a point-to-orifice-plate configuration and a charge reduction chamber that can hold up to 4 Nuclespot ionizers (Model P-2042, NRD Inc.). The 2 chambers are partitioned by an orifice plate. To optimize the particle transmission efficiency of the prototype, a systematic study was performed on the generator by varying the system setup and operation. Two key dimensions of the generator setup, the orifice diameter and the distance from the capillary tip to the orifice plate, were varied. Fluorescence analysis was applied to characterize the loss of ES-generated particles at different locations of the prototype. It was found that particle loss in the generator could be reduced by either increasing the orifice diameter or decreasing the distance between the capillary tip and the orifice plate. Increasing either the total radioactivity of the ionizers or the flowrate of the particle carrier gas also further decreased the particle loss in the system. The maximum particle transmission efficiency of 88.0% was obtained with the spray chamber fully opened to the charge reduction chamber, the capillary tip at the same level as the orifice plate, and 4 bipolar ionizers installed